2006
DOI: 10.1523/jneurosci.0037-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Astrocytic Gap Junctional Coupling on Potassium Buffering in the Hippocampus

Abstract: Astrocytic gap junctions have been suggested to contribute to spatial buffering of potassium in the brain. Direct evidence has been difficult to gather because of the lack of astrocyte-specific gap junction blockers. We obtained mice with coupling-deficient astrocytes by crossing conditional connexin43-deficient mice with connexin30 Ϫ/Ϫ mice. Similar to wild-type astrocytes, genetically uncoupled hippocampal astrocytes displayed negative resting membrane potentials, time-and voltage-independent whole-cell curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
579
3
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 517 publications
(621 citation statements)
references
References 44 publications
33
579
3
6
Order By: Relevance
“…The importance of astrocytes and morphological contacts formed between astrocytic processes and synapses is apparent as astrocytes and astrocyte-conditioned media promote synapse formation (Pfrieger and Barres, 1997;Ullian et al, 2001) and both LTP and LTD are affected by astrocytes acting through several mechanisms. Astrocytes directly regulate NMDA-receptor-dependent LTP and plasticity through glial-derived D-serine (Yang et al, 2003;Panatier et al, 2006), ATP and adenosine (Pascual et al, 2005;Fields and Burnstock, 2006), glutamate reuptake and release (Haydon and Carmignoto, 2006) and extracellular K + handling (Wallraff et al, 2006;Djukic et al, 2007;Ge and Duan, 2007). Our findings on activity-dependent astrocyte differentiation by ATP and LIF in vitro and the observation of behavioral impairments in LIF −/− mice (Pechnick et al, 2004) and LIF over-expressing mice (Pechnick et al, 2004) suggest that LIF may be important in hippocampal development and plasticity in vivo through astrocytes.…”
Section: Discussionmentioning
confidence: 59%
“…The importance of astrocytes and morphological contacts formed between astrocytic processes and synapses is apparent as astrocytes and astrocyte-conditioned media promote synapse formation (Pfrieger and Barres, 1997;Ullian et al, 2001) and both LTP and LTD are affected by astrocytes acting through several mechanisms. Astrocytes directly regulate NMDA-receptor-dependent LTP and plasticity through glial-derived D-serine (Yang et al, 2003;Panatier et al, 2006), ATP and adenosine (Pascual et al, 2005;Fields and Burnstock, 2006), glutamate reuptake and release (Haydon and Carmignoto, 2006) and extracellular K + handling (Wallraff et al, 2006;Djukic et al, 2007;Ge and Duan, 2007). Our findings on activity-dependent astrocyte differentiation by ATP and LIF in vitro and the observation of behavioral impairments in LIF −/− mice (Pechnick et al, 2004) and LIF over-expressing mice (Pechnick et al, 2004) suggest that LIF may be important in hippocampal development and plasticity in vivo through astrocytes.…”
Section: Discussionmentioning
confidence: 59%
“…Through this mechanism, astrocytes can facilitate spatial buffering of K + and spatial allocation of neurotransmitters and inter-astrocyte signalling over greater distances (Giaume et al, 1997;Hansson et al, 2000;Sontheimer et al, 1990;Wallraff et al, 2006). Therefore, the changes in Cx43, Kir channels and Aqp4 gene expression reported in this study are likely to have a significant impact on neuronal function and network activity during and after HA in the brain.…”
Section: Discussionmentioning
confidence: 72%
“…The downregulation of Cx43 observed in FACS-purified GFAP-EGFP + astrocytes was analyzed further, because of: (i) the fundamental physiological role of Cx43 as the main gap junction channel in astrocytes (Dermietzel et al, 1991;Iacobas et al, 2004); (ii) the downregulation of Cx43 also found in cortical tissue of hyperammonemic mice (present study); (iii) the clustering and apparent loss of connectivity between EGFP + astrocytes along the brain vasculature of hyperammonemic animals (present study); and (iv) the importance of Cx43 for potassium homeostasis in the brain (Kozoriz et al, 2006;Wallraff et al, 2006). In addition to Cx43 and gap junctions, potassium homeostasis is also regulated by astrocytic inward-rectifying potassium channels, which exist as Kir4.1 homodimers and Kir4.1/Kir5.1 heterodimers (Hibino et al, 2004;Kofuji et al, 2002;Kucheryavykh et al, 2007;Neusch et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…CX43/CX30 double knockout leads to impaired potassium clearance and disrupts synaptic transmission and plasticity (Pannasch et al, 2011; Wallraff et al, 2006). CX43/CX30 double knockout also causes astrocyte endfeet edema and weakens the blood‐brain barrier (Ezan et al, 2012).…”
Section: Potential Therapeutic Targets In Astrocytesmentioning
confidence: 99%